The Effect of Financial Audit Guidelines and Fraud Detection Awareness on Quality Audit Results During the COVID-19 Pandemic - Nendiarie, Sonly; Musyarofah, Siti; Tarjo, Tarjo (Badan Pemeriksa Keuangan Republik Indonesia, 2022)
Many elements of society have experience disadvantages as a result of an array of problems in financial reporting. Given the preceding situation, a financial statement audit conducted by the auditor as an independent party is expected to achieve reliable audit quality. However, under the current situation of the pandemic, the auditor faced numerous challenges that have never been encountered before in carrying out audits. An Auditor must be more creative in conducting audits and comply with audit standards. The possibility of fraud risk in financial audits is also greater during the pandemic. This study aims to explain the role of financial audit guidelines and fraud detection awareness in providing quality audit results during the COVID-19 pandemic. This research was conducted upon auditors of BPK Representative of East Java province who were involved in financial audits. There were 91 respondents involved in this study. The research method applied multiple regression data analysis with the Partial Least Squares (PLS) approach through the help of the SmartPLS 3.0 program. The study would produce financial audit guidance variables and fraud detection awareness that will significantly positively affect quality audit results.